Pengaruh Training Flight Terhadap Keselamatan Penerbangan di Airnav Indonesia Unit Bandar Lampung - Fairlya Anissanadhea; Surya Tri Saputra; Ahsonul Anam (Jurnal Manajemen Dirgantara, 2024)
This research aims to quantitatively analyze the influence of training flight on flight safety in the environment of the Airnav Indonesia at the Bandar Lampung Unit Office. This study originates from an incident where a training flight did not follow ATC’s instructions, resulting in the failure to maintain minimum separation and endangering aviation safety. The quantitative method is employed with data collection through a questionnaire focusing on the perceptions and experiences of ATC regarding the impact of flight training on flight safety. The respondents in this study are air traffic controllers (ATCs) at Airnav Indonesia Bandar Lampung. The collected data will be analyzed to assess the extent to which flight training contributes to the level of flight safety. The research results indicate that the training flight received a score of 342 with a percentage of 68.4%, while flight safety achieved a score of 433 with a percentage of 86.6%. Data analysis shows a strong relationship between training flight and flight safety, with a correlation coefficient of 0.755 and a determination coefficient of 0.571. A simple linear regression test indicates a significant influence between training flight and flight safety, with the equation Y = 21.963 + 0.624X. The research outcomes are expected to provide a deeper understanding of the tangible impact of flight training on various aspects of flight safety. Utilizing a questionnaire-based approach, the study will highlight ATC's perceptions regarding of training flight in influencing the improvement of flight safety. The findings are anticipated to contribute to the development of more effective flight training policies, considering significant factors that influence flight safety. The practical implications of this research are expected to offer data-driven recommendations for Airnav Indonesia Bandar Lampung to enhance the effectiveness of flight training programs and ultimately optimize flight safety at the local level.